MULTIMODAL CONTENT ANALYSIS OF 21ST CENTURY SKILLS IN AN ENGLISH TEXTBOOK - Murtadho, Muhammad Ali Arif; Eryansyah, Eryansyah; Silvhiany, Sary (English Review: Journal of English Education, 2024)
English textbooks are a valuable tool for promoting the development of 21st century skills. Meanwhile, multimodal texts in textbooks are employed by authors to convey meaning through verbal and visual modes, thus necessitating the adoption of multimodal analysis as the most efficacious method for its elucidation. Regrettably, there exists a dearth of literature concerning the application of this approach for analyzing textbooks. To fill this gap, the study examined 21st century skills in an English textbook. This study used content analysis with multimodal social semiotic approach. The subject of the study was an English textbook “English for Nusantara” for the seventh-grade students. The result shown that critical thinking and problem-solving skill was the most frequent type. However, the study did not find any mention of media literacy, and there were only a few instances of economic literacy and global awareness. It is suggested that future revisions should include them. Moreover, English teachers are urged to actively participate in the process of textbook selection and augment the instructional materials with supplementary resources to mitigate any inadequacies of the textbook.